Exploring Career Preparation: The Role of Freelance Job, Soft Skill Development, and Interest in Entrepreneurship for Generation Z (Study in Semarang) - Della Christine Parhusip; Artha Febriana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The aim of this study is to measure the influence and contribution of the freelance job, soft skill development, and interest in entrepreneurship on Generation Z career preparation in Semarang City. Using a quantitative approach, this study utilized a five-point Likert scale to measure the questionnaire on primary data. A total of 112 respondents’ survey data was tested using the purposive sampling method and analyzed with the classical assumption test and multiple regression in SPSS Statistics 25. The result shows that the freelance job is found to have influenced career preparation significantly and positively. It was also found that soft skill development influenced career preparation significantly and positively. Additionally, interest in entrepreneurship has a significant and positive influence on career preparation.